Industry 4.0: a challenge of competition - Antunes, Joaquim (2018)
Introduction: The value creation in industry in developed countries is being driven by the fourth stage of industrialization, denominated by Industry 4.0. The new industrial revolution will be motivated by next-generation information technologies such as Internet of Things (IoT), cloud computing, Big Data and data analysis, robotics, mobile computing, simulation and modelling, cyber-physical systems, among others. This opens new horizons for industry, but the challenges are countless creating difficulties for companies in the adoption of these technologies. Objectives: To make a powerful and deep literature revision pursuing a technical analysis of the Industry 4.0 requirements. Methods: We will address the main risks and challenges associated with IoT and define the regional attractiveness measures as growth drivers that leaders must put in place to appeal for companies chasing 4.0. Results: IoT joins the digital world and the physical world being considered the next generation network or the future Internet. It allows to give life and communication capacity either to living beiings or to inanimate objects. IoT's intervention in Industry 4.0 im extreme, with a continuous interconnection of the digital and physical domain. Conclusions: Portugal's growth prospects will increasingly depend on policies that enable the economy to compete successfully and create new income opportunities. At the moment, there are structural bottlenecks that continue to curb growth and exacerbate vulnerabilities. Solving some of these problems will now lay the foundation for solid growth in the coming years, but this calls for a renewal of the impetus for structural reforms. Industry 4.0, can contribute significantly to reducing regional asymmetries. But in the longer term, skills will need to be improved to foster development and reduce the high levels of such inequalities.